2002
DOI: 10.1152/japplphysiol.00116.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic adaptation of individual human diaphragmatic myofibers to severe COPD

Abstract: To assess the effect of severe chronic obstructive pulmonary disease (COPD) on the ability of human diaphragmatic myofibers to aerobically generate ATP relative to ATP utilization, we obtained biopsy specimens of the costal diaphragm from seven patients with severe COPD (mean +/- SE; age 56 +/- 1 yr; forced expiratory volume in 1 s 23 +/- 2% predicted; residual volume 267 +/- 30% predicted) and seven age-matched control subjects. We categorized all fibers in these biopsies by using standard techniques, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 48 publications
12
98
2
3
Order By: Relevance
“…Sanchez et al (78) reported a general loss in diameter of both type I and type II fibers. This was also addressed by Levine et al (37) and in the recent work of Stubbings et al (84). Both report significant reductions (41% in Ref.…”
Section: Changes In Fiber Phenotype and Sizementioning
confidence: 63%
See 2 more Smart Citations
“…Sanchez et al (78) reported a general loss in diameter of both type I and type II fibers. This was also addressed by Levine et al (37) and in the recent work of Stubbings et al (84). Both report significant reductions (41% in Ref.…”
Section: Changes In Fiber Phenotype and Sizementioning
confidence: 63%
“…Multiple studies from several laboratories have shown statistically significant increases in the relative proportions of type I fibers in the costal diaphragm (18,37,38,40,84), with two of the laboratories demonstrating a strong correlative relationship of the proportion of type I oxidative fibers with deterioration of lung function (40,84). Figure 2, A and B, illustrates the contrasting differences in fiber populations in control vs. severe emphysema patients.…”
Section: Changes In Fiber Phenotype and Sizementioning
confidence: 96%
See 1 more Smart Citation
“…In the COPD patient group, FOXO‐1 protein expression was higher in limb muscles than in respiratory muscles, while this difference was not found in controls 46. Interestingly, the respiratory muscles of COPD patients show an opposite fibre type shift compared with limb muscles, that is, towards more type I fibres 47, 48. This will have implications for the expression levels of constituents of atrophy signalling pathways 22, 49.…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 91%
“…As indicated by LEVINE et al [28], differences may exist between the adaptation of the diaphragm to EMP in animals and the human with COPD. In general, it appears that the hamster diaphragm adapts by increasing the CSA of both type I and II fibres without fibre transformation, whereas the human diaphragm adapts with type I fibre atrophy that may or may not be associated with a type II to I fibre transformation.…”
Section: Respiratory Musclesmentioning
confidence: 94%